Penerapan Teori A.C.T.O.R.S pada Pemberdayaan Masyarakat di Desa Wisata “Ekowisata Burai” Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Maulana, Maulana; Yunindyawati, Yunindyawati; Taqwa, Ridhah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
"Burai Ecotourism Village" in South Sumatra Province, Indonesia, underwent a positive transformation through the Burai Village Tourism Program (Bu Dewi) initiated by PT Pertamina EP Asset 2 Prabumulih Field. This program successfully involves the community in village development by giving authority, increasing self-confidence, building trust, providing opportunities, handing over responsibility to the community, and providing support from various parties. This research aims to analyze community empowerment efforts in the program, using the A.C.T.O.R.S Theory by Macaulay & Cook (1997). Through descriptive qualitative research methods, this study focuses on the Tourism Village "Burai Ecotourism," Tanjung Batu District, Ogan Ilir Regency. The results of the analysis showed that Bu Dewi's program successfully involved the community in the development of the village by giving authority, increasing self-confidence and competence, building trust, providing opportunities, handing over responsibility to the community, and providing support from various parties.